2014
DOI: 10.5505/tjtes.2014.65392
|View full text |Cite
|
Sign up to set email alerts
|

Blunt renal trauma in children: a retrospective analysis of 41 cases

Abstract: ÖZET AMAÇ: Çocukluk çağında, künt karın travma sonrası gelişen böbrek yaralanmaları ameliyatsız yöntemle başarıyla tedavi edilmektedir. Bu çalışmada, çocuklarda künt karın travmasına bağlı böbrek yaralanması olan olgular değerlendirildi. GEREÇ VE YÖNTEM:Bu çalışmada 2000 ile 2012 yılları arasında künt travmaya bağlı böbrek yaralanması nedeniyle çocuk cerrahi servisinde takip edilen olguların bilgileri geriye dönük olarak değerlendirildi. Olgular demografik özellikleri, klinik, tedavi ve sonuçları açısında değe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The majority of children with blunt renal trauma can be managed conservatively even with high-grade injuries. [ 13 14 15 16 17 18 ] Our study confirmed the previous findings of low pediatric nephrectomy rates (0%–3.2%). [ 7 17 19 20 ]…”
Section: Discussionsupporting
confidence: 90%
“…The majority of children with blunt renal trauma can be managed conservatively even with high-grade injuries. [ 13 14 15 16 17 18 ] Our study confirmed the previous findings of low pediatric nephrectomy rates (0%–3.2%). [ 7 17 19 20 ]…”
Section: Discussionsupporting
confidence: 90%
“…According to the literature, the prevalence of surgical therapy ranges from 8 to 31% and the prevalence of conservative treatment is from 70 to 92% [22] . Recent investigations have found that the surgery ratio is frequently low.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the blunt kidney injuries in children (85%) are low-grade. 1 Compared to adults, children have weaker abdominal muscles and less protective chest walls. In addition, their kidneys are moving, placed lower in the body, the ratio of kidney and body is large, and perirenal fat tissue is less.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, their kidneys are moving, placed lower in the body, the ratio of kidney and body is large, and perirenal fat tissue is less. [1][2][3] All these anatomical differences cause more kidney injuries in children with traumas compared to adults. Renal injuries detected via evaluation of patients physical examination, laboratory tests, and imaging methods in emergency department.…”
Section: Introductionmentioning
confidence: 99%